Rancang Bangun Sistem Kontrol Mekanisme Pelacakan Matahari Beserta Fasilitas Telekontrol Hemat Energi - Midriem Mirdanies; Rizqi Andry Ardiansyah; Hendri Maja Saputra; Aditya Sukma Nugraha; Estiko Rijanto; Adi Santoso (National Research and Innovation Agency, 2011)
Solar energy produced by concentrated solar heat collector panels requires tracking mechanisms for a more optimal direction. This paper presents the design and construction of a low energy solar tracking control system with telecontrol facilities. To accelerate the movement of the panel in always adjusting itself to the direction of the sun, a combination of the timer and light sensor was used. In this control system, the reference signal is taken from two pieces of light sensors while the feedback is taken from the position and temperature sensors. The program has been developed using C language and was implemented on the microcontroller ATMega8535 as the brain of the system. Telecontrol facilities for monitoring the data to a computer uses transceiver modules via RS-232 connection. A DC motor having power capacity of 0.74 watts was used and was clutched with 1:7,300 gearbox ratio. Experiments on light sensor characteristics and simulated movement of the panel were carried out. From the light sensor experiment it can be concluded that the sensor produces 0-4 volt output signal when bright 3.3-3.9 volts, when cloudy and 1.5-3.3 volts when sunny. From the simulation of panel movement, it is known that the solar tracking control system moves the panel and tracks the direction of the sun movement.